Embedding Mindfulness into Sport Specific Training: Effects on Attentional Control in Adolescent Wushu Athletes - Pengfei Zhang; Setiyo Hartoto; Heryanto Nur Muhammad; Farruh Ahmedov (Journal of Sport Science and Education, 2025)
Attentional control is a critical cognitive component in precision-based sports such as wushu, where athletes must coordinate complex motor actions with sustained focus. While mindfulness training has been widely studied in sport psychology, its integration into sport-specific training contexts remains limited, particularly in martial arts. This study aimed to examine the effect of embedding mindfulness practices into regular wushu training on athletes’ attentional control. Methods: A pre-experimental one-group pretest–posttest design was employed involving 23 adolescent wushu athletes (aged 16–20 years) with at least two years of training experience. Participants underwent a four-week mindfulness-integrated training program (3 sessions/week, 30 minutes/session). Attentional control was measured using the Attention Control Scale (ACS). Data were analyzed using descriptive statistics, normality tests, paired sample t-tests, and effect size (Cohen’s d). Result: The results showed a significant improvement in attentional control scores (p < 0.001), with mean scores increasing from 60.30 to 75.91. The effect size was large (d = 3.92), indicating substantial practical impact. Conclusion: Embedding mindfulness into sport-specific training may effectively enhance attentional control in wushu athletes. However, due to the absence of a control group, findings should be interpreted cautiously. Future studies using stronger experimental designs are recommended.